2023
DOI: 10.1002/ctm2.1158
|View full text |Cite
|
Sign up to set email alerts
|

CircZSWIM6 mediates dysregulation of ECM and energy homeostasis in ageing chondrocytes through RPS14 post‐translational modification

Abstract: Background Circular RNAs (CircRNAs) are important and have different roles in disease progression. Herein, we aim to elucidate the roles of a novel CircRNA (CircZSWIM6) which is upregulated in ageing chondrocytes. Methods We verified the roles of CircZSWIM6 in senescent and osteoarthritis (OA) development in vitro through CircZSWIM6 knockdown and overexpression. RNA pulldown assay and RNA binding protein immunoprecipitation were performed to identify the interaction between CircZSWIM6 and Ribosomal protein S14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
(86 reference statements)
0
8
0
Order By: Relevance
“…As a major post-translational modification, ubiquitylation regulates several physiological processes including chondrocytes metabolism. 15,47,59 CircARPC1B knockdown increased Vimentin ubiquitination, whereas circARPC1B overexpression decreased its ubiquitination. Furthermore, rescue experiments further demonstrated that circARPC1B functions as a Vimentin stabilisation enhancer to prevent chondrocyte degradation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…As a major post-translational modification, ubiquitylation regulates several physiological processes including chondrocytes metabolism. 15,47,59 CircARPC1B knockdown increased Vimentin ubiquitination, whereas circARPC1B overexpression decreased its ubiquitination. Furthermore, rescue experiments further demonstrated that circARPC1B functions as a Vimentin stabilisation enhancer to prevent chondrocyte degradation.…”
Section: Discussionmentioning
confidence: 95%
“…CircARPC1B altered the expression level of Vimentin protein but not its mRNA level, implying that circARPC1B can influence post‐translational modifications of Vimentin. As a major post‐translational modification, ubiquitylation regulates several physiological processes including chondrocytes metabolism 15,47,59 . CircARPC1B knockdown increased Vimentin ubiquitination, whereas circARPC1B overexpression decreased its ubiquitination.…”
Section: Discussionmentioning
confidence: 99%
“…AMPK is an important regulator of cellular energy homeostasis, which can regulate cell growth, differentiation and apoptosis by affecting signaling pathways such as mTOR and p53. 107,135 The classic mechanism by which circRNA functions is the ceRNA network. There have demonstrated that circ_002581 regulated the PTEN-AMPK-mTOR pathway via acting as a sponge for miR-122, 117 circWHSC1 modulated the FASN-AMPK-mTOR axis by sponging miR-195-5p, 118 circ_0057558 acted as a miR-206 sponge to activate the ROCK1/AMPK signaling.…”
Section: Ampk Signaling Pathwaymentioning
confidence: 99%
“…AMPK is an important regulator of cellular energy homeostasis, which can regulate cell growth, differentiation and apoptosis by affecting signaling pathways such as mTOR and p53 107,135 …”
Section: Circular Rnas Regulate Cellular Senescence Via Various Pathwaysmentioning
confidence: 99%
“…Although the various biological functions and molecular mechanisms of cir-cRNAs remain largely uncharacterized, emerging evidence suggests that they participate in the development of different diseases (Li et al 2019). CircRNAs have recently been shown to be involved in OA (Gong et al 2023), but little is known about the importance and roles of circRNAs in TMJ maintenance and OA pathogenesis.…”
Section: Introductionmentioning
confidence: 99%